Criticism in the Borderlands : Studies in Chicano Literature, Culture, and Ideology - Hinojosa, Rolando; Saldívar, Jose David; Calderón, Hector (Book collections on Project MUSE., 1991)
This pathbreaking anthology of Chicano literary criticism, with essays on a remarkable range of texts-both old and new-draws on diverse perspectives in contemporary literary and cultural studies: from ethnographic to postmodernist, from Marxist to feminist, from cultural materialist to new historicist.The editors have organized essays around four board themes: the situation of Chicano literary studies within American literary history and debates about the "canon"; representations of the Chicana/o subject; genre, ideology, and history; and the aesthetics of Chicano literature. The volu.